Pulmonary Tuberculosis and Influential Factors in the Working Area of Puskesmas Darul Imarah Kabupaten Aceh Besar 2015-2016 - Rosdiana, Eva; Ginting, Daniel; G., Vierto Irennius (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2018)
Tuberculosis is one of the ten causes of death throughtout the world. Indonesia is ranked the third of tuberculosisin 2015 after China and India. It is still abigÂ  problem in the developing countries. The results of the survey in Darul Imarah Puskesmas in 2016 found that the case increased from the previous year to 42 cases in which 2 of them were relapse cases, 2 of the died and one of them extra pulmonary tuberculosis. The objective of the research was to find out some factors which influenced the incidence of pulmonary tuberculosis the research used mixed method (quantitative-qualitative) with case-control design. The samples were 41 respondents in case group dan 41 respondents in control group (the ratio of 1:1), taken by using simple random sampling technique. Chi square test was used for statistic test at the significance level of 95%; the data were analyzed by using multivariate analysis with logistic regression test. The result of the research showed that there was the influence of the variable of ventilation at p-value = 0.008 and OR = 3.801 (95%CI: 1.345-12.393) and the variable of smoking habit at p-value = 0.004 and OR = 10.676 (95%CI: 2.120-53.748). The result of multivariate analysis showed that the variable which the most dominant influence was smoking habit at p-value = 0.008 and OR = 9.822 (95%CI: 1.833-52.614) which indicated that a person who had smoking habit, and ventilation and lighting which had not fulfilled the requirement would have 81.9% of the opportunity to have the risk for being affected by tuberculosis. It is recommended that the health care providers at Puskesmas provide counseling about tuberculosis and eliminate peopleâs stigma about tuberculosis and help DOTS program in finding new case in tuberculosis in society so that the incidence of tuberculosis can be handled properly.Keywords: pulmonary tuberculosis, ventilation, Â smoking habit